Management of recurrent aphthous ulceration with iron deficiency anemia : a case report - Yuskhaidir, Yuskhaidir; Radithia, Desiana; Ernawati, Diah S. (Hasanuddin University, 2019)
Objective: Recurrent aphthous Ulceration (RAU) is a common oral mucosal disease characterized by recurrence and painful ulcers in non-keratinized oral mucosa.. A teenage girl aged 18 years 7 months comes with complaints of a lot of ulcers in the oral cavity. The patient said that she had had ulcers since 3 years ago, had no history of allergies, and with a weight that dropped below normal according to BMI standards. From intra oral examination multiple ulcers appear on the labial mucosa, buccal mucosa, painful gingiva and atrophy on the tongue.Methods : Patients undergo complete blood tests with Hb results of 10.8 g / dL (N: 11.7â€“15.3 g / dL), Eosinophils 5% (N: 2-4%), Neutrophils 42%, lymphocytes 42%, monocytes 8%, hematocrit 33%, MCV 68 fL, MCH 21 pg, Â MCHC 31 g / dL.Results : Based on history, clinical examination and laboratory examination, a diagnosis of recurrent aphthous ulceration related to iron deficiency anemia can be established with a differential diagnosis of minor type recurrent aphthous stomatitis. The results of the examination with a TIBC value of 437.1 H, Serum iron 48.61 L, and ferritin 62.71 L. Patients treated with non-steroidal anti-inflammatory mouthwash and multivitamins. Patients are instructed to increase intake of foods containing iron, fruits and vegetables and avoid fatigue or adequate rest.Conclusions : Therapy RAU with a food-based approach and a drug-based approach chlorine dioxide, Iron Polymaltose Complex, folic acid and vitamin cÂ Key words : Recurrent aphthous ulceration, hemoglobin, iron deficiency anemia